Clinical Case Reports on the acceptability and tolerance of a High‐Energy whey peptide‐based Pediatric oral nutritional supplement in children aged over 12 months. Issue 10 (5th October 2021) - Simpson, Kathryn
Abstract: The nutritional management of the complex needs of children with impaired gastrointestinal function can be challenging, using a high‐energy pediatric whey‐based peptide formula in clinical practice demonstrates its role in managing symptoms. Abstract : The nutritional management of the complex needs of children with impaired gastrointestinal function can be challenging, using a high‐energy pediatric whey‐based peptide formula in clinical practice demonstrates its role in managing symptoms.